The inhibitory influence of adipose tissue-derived mesenchymal stem cell environment and Wnt antagonism on breast tumour cell lines - Visweswaran, M.; Arfuso, Frank; Dilley, R.; Newsholme, P.; Dharmarajan, Arunasalam (Pergamon, 2017)
Tumours exhibit a heterogeneous mix of cell types that reciprocally regulate their growth in the tumour stroma, considerably affecting the progression of the disease. Both adipose-derived mesenchymal stem cells and Wnt signalling pathway are vital in driving breast tumour growth. Hence, we examined the effect of secreted factors released by adipose-derived mesenchymal stem cells, and further explored the anti-tumour property of the Wnt antagonist secreted frizzled-related protein 4 (sFRP4) on MCF-7 and MDA-MB-231 breast tumour cells. We observed that conditioned medium and extracellular matrix derived from adipose-derived mesenchymal stem cells inhibited tumour viability. The inhibitory effect of the conditioned medium was retained within its low molecular weight and non-protein component. The conditioned medium also induced apoptosis accompanied by a decrease in the mitochondrial membrane potential in tumour cells, Furthermore, it downregulated the protein expression of active ß-catenin and Cyclin D1, which are major target proteins of the Wnt signalling pathway, and reduced the expression of anti-apoptotic protein Bcl-xL. The combination of conditioned medium and sFRP4 further potentiated the effects, depending on the tumour cell line and experimental assay. We conclude that factors derived from conditioned medium of adipose-derived mesenchymal stem cells and sFRP4 significantly decreased the tumour cell viability and migration rates (MCF-7), accompanied with an enhanced apoptotic activity through inhibition of canonical Wnt signalling. Besides giving an insight to possible paracrine interactions and influence of signalling pathways, reflective of a breast tumour microenvironment, this study emphasises the utilization of cell free-secreted factors and Wnt antagonists to improve conventional anti-cancer strategies.